To Allen Forte from His Former Advisees: Tributes and Reminiscences - David Carson Berry (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
Testimonials are collected from forty-two former doctoral advisees of Allen Forte, whose Yale graduation dates range from 1968 to 2002. Although the style and focus of individual tributes vary, many convey something about Forte, both professionally and personally, at the time in which the advisee studied with him. The results are ordered chronologically (by Ph.D. dates) so that collectively they suggest the evolution of Forte himself, as well as North American music theory, across the decades. The contributors include (in alphabetical order): Baker, James M.; Ballan, Harry R.; Beach, David W.; Bergman, Rachel; Bernard, Jonathan W.; Berry, David Carson; Black, Leslie; Boss, Jack F.; Brown, Stephen C.; Chapman, Alan; Check, John; Chrisman, Richard; Damschroder, David A.; Ewell, Philip; Galand, Joel; Girton, Irene M. [Levenson]; Graziano, John; Greer, Taylor A.; Hamao, Fusako; Hanson, Jens L.; Harrison, Daniel; Horlacher, Gretchen; Kowalke, Kim H.; Krebs, Harald; Latham, Edward D.; McNamee, Ann K.; Moreno, Jairo; Neumeyer, David; Nolan, Catherine; Rothgeb, John; Rothstein, William; Russom, Philip; Schmalfeldt, Janet; Schwanauer, Stephan M.; Shaftel, Matthew R.; Spicer, Mark S.; Stein, Deborah; Straus, Joseph N.; Wason, Robert W.; Wheaton, J. Randall; Yeston, Maury; and Yih, Annie K. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).